Effects of dietary nitrate supplementation on a battery of reliable soccer-specific tests - Ranchordas, M. K. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
Dietary nitrate supplementation has been found to lower the oxygen cost of submaximal exercise, increase time to exhaustion, and enhance performance in time trials. The effect of nitrate supplementation on soccer-specific performance is unknown, so the purpose of this study was to investigate the effects of dietary nitrates on a battery of reliable soccer-specific tests commonly used in professional soccer. Fourteen welltrained soccer players (stature, 1.75 ± 0.06 m; body mass, 74.8 ± 5.6 kg; sum of 7 skinfolds, 51.2 ± 10.2 mm) who trained for at least 10 hours per week participated in this study. In a randomized single-blind crossover design players consumed either 140 ml/day of concentrated beetroot juice or a placebo daily for 3 days prior and 90 min before completing a battery of commonly used reliable soccer-specific tests separated by a 7-day washout. T he test battery consisted of the pro-agility test, 10-m and 30-m sprints, a countermovement jump, the Yo-Yo Intermittent Recovery Level 2 Test, and blood lactate was taken within 2 min of finishing the Yo-Yo test. No changes in performance were observed in the concentrated beetroot juice vs. placebo on the pro-agility test (5.54 ± 0.42 vs. 5.47 ± 0.37 s, p > .05), 10-m (1.68 ± 0.11 vs. 1.71 ± 0.09 s, p > .05) and 30-m sprints (4.28 ± 0.19 vs. 4.32 ± .021 s, p > .05), and countermovement jumps (34.49 ± 10.35 vs. 36.41 ± 5.26, p > .05). Distance covered during the Yo-Yo Intermittent Recovery Level 2 Test was greater in the beetroot condition compared to the placebo (698 ± 115 vs. 684 ± 109 m, p < .007 ), but no changes in blood lactate measured at the end of the Yo-Yo test were observed (10.8 ± 2.1 vs. 11.0 ± 2.2 mmol/L, p > .05). These data suggest that ingesting 140 ml/day of concentrated beetroot juice for 3 days and 90 min prior to testing can increase the distance covered on the Yo-Yo Intermittent Recovery Level 2 Test by 1.9%.